Can I Leave the House? A Coded Analysis of the Interpretation of the Reasonable Excuse Provision by NSW Police During the COVID-19 Lockdown. (September 2021) - Mostyn, Ben; Kinchin, Niamh
This article looks at the recent Public Health (COVID-19 Restrictions on Gathering and Movement) Order 2020, which was in force in New South Wales from 31 March 2020 to 14 May 2020. The order allowed police to fine people who left their houses without a 'reasonable excuse'. This article considers the confusion around the order in the community and upper levels of the government. Publicly available information about the fines issued by the police is analysed and it is argued that an overly narrow application of the order by police meant that its application was not reasonably proportionate to the authorising legislation, the Public Health Act 2010 (NSW). It is concluded that if future lockdowns are required, care will need to be taken to ensure that Ministerial orders are crafted in line with the legislation and that police officers clearly understand their operation.